2019
DOI: 10.1159/000507023
|View full text |Cite
|
Sign up to set email alerts
|

CREB Protects against Temporal Lobe Epilepsy Associated with Cognitive Impairment by Controlling Oxidative Neuronal Damage

Abstract: Background: Cognitive dysfunction as a common comorbidity of epilepsy often manifests as learning and memory impairments in patients with temporal lobe epilepsy (TLE). The pathogenetic molecular mechanisms underlying epilepsy-associated cognitive dysfunction are incompletely understood. We investigated the role of cAMP response element binding protein (CREB) and its downstream signaling pathways in the pathogenesis of cognitive impairment in mice with TLE. Methods: Plasmid vectors of CREB-specific short-hairpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…Activation of CREB is widely implicated in neuronal survival and has long been known to be important for the formation of memories. On the opposite, CREB signaling dysfunction is associated with several neurodegenerative diseases, including AD [31] and brain injury models [32]. These results confirm that IGF1Rs deficiency modulates the expression of key regulators of brain higher functions.…”
Section: Effects Of Igf1r Deficiency On Synaptic Plasticity Markerssupporting
confidence: 55%
“…Activation of CREB is widely implicated in neuronal survival and has long been known to be important for the formation of memories. On the opposite, CREB signaling dysfunction is associated with several neurodegenerative diseases, including AD [31] and brain injury models [32]. These results confirm that IGF1Rs deficiency modulates the expression of key regulators of brain higher functions.…”
Section: Effects Of Igf1r Deficiency On Synaptic Plasticity Markerssupporting
confidence: 55%
“…The increased mRNA expression of CREB-1 in the second hit PTZ group reflects the plausible role of CREB-1 in epilepsy as well as suggest that memory is impaired upon PTZ administration. Acknowledging the role of CREB in TLE associated cognitive decline (Xing et al, 2019), we hypothesize that CREB-1 plausibly contribute to the memory impairment in the second hit PTZ group as evidenced by an increased expression.…”
Section: Second Hit Ptz Induced Inflammatory Response Is Alleviated Bmentioning
confidence: 93%
“…Anti-HMGB1 mAb Rescued Second Hit PTZ Induced Modulation in CREB-1 and NPY CREB is a transcription factor with established role in plasticity (Lonze and Ginty, 2002) and alteration in the level of CREB has been implicated in several psychiatric diseases (Carlezon et al, 2005). In addition to that, CREB has been well acknowledged for its role in memory formation, neuronal plasticity and long-term memory formation and regulates the genes (BDNF, C-FOS) that are crucial for memory formation (Xing et al, 2019). The increased mRNA expression of CREB-1 in the second hit PTZ group reflects the plausible role of CREB-1 in epilepsy as well as suggest that memory is impaired upon PTZ administration.…”
Section: Second Hit Ptz Induced Inflammatory Response Is Alleviated Bmentioning
confidence: 99%
“…Among these compounds, there are extensive publications of the neuroprotective effects of MitoQ against epileptic condition. It has demonstrated that treatment with MitoQ significantly rescues learning and memory deficits in pilocarpine-induced mice model of temporal lobe epilepsy via activation of cAMP response element-binding protein (CREB) [ 62 ]. The beneficial effect of MitoQ in the alleviation of memory decline is also found in Angelman syndrome [ 63 ], which is associated with epileptic pathology, and it is demonstrated that its therapeutic response is likely through reducing superoxide generation and suppressing neuronal apoptosis.…”
Section: Mitochondrially Targeted Antioxidants As Neuroprotective mentioning
confidence: 99%